Protein Changes during Malting of Barley using Novel Lab-on-a-Chip Technology in Comparison to two-dimensional Gel Electrophoresis - Klose, Christina; Schehl, Beatus D.; Arendt, Elke K. (BrewingScience, 2008)
During the malting process storage proteins are degraded by proteolytic enzymes into small peptides and amino acids. The activity of these enzymes was measured at various stages during malting of barley and was found to be increased. To visualize proteolytic degradation, proteins of unmalted, germinating and malted grains were fractionated. After extracting the proteins on the basis of their solubility (Osborne fractionation) protein fractions were analysed using a Lab-on-a-Chip technique, which separates the proteins, based on their molecular weight, by capillary electrophoresis. This new technique for the analysis of proteins was supported by using two-dimensional gel electrophoresis. In addition, amino acid analysis on barley and barley malt was carried out. In general a degradation of the proteins to small peptides and amino acids could be observed in all fractions. In the albumin and globulin fraction also a protein increase was observed, which is due to the fact that these fractions contain the majority of the metabolically active proteins. The Lab-on-a-Chip analysis technique was found to be appropriate for analysis of degrading or increasing proteins, as it revealed rapid, repeatable and reliable results, which could be validated by using common protein analysis techniques such as two-dimensional gel electrophoresis and amino acid analysis.